PERSEPSI MASYARAKAT TERHADAP PENGOBATAN TRADISIONAL BERDASARKAN PERBEDAAN JENIS KELAMIN - Djamaluddin, Agus; Putra, Risa Kota; Ratnasari, Dewi (Journal of Holistic and Health Sciences (Jurnal Ilmu Holistik dan Kesehatan), 2020)
Background: People in Indonesia, especially people who reside in Purwakarta Regency have been to generation, have used traditional ingredients as an alternative treatment, and lately increasingly rampant products made from herbs on the market. These traditional medicine users include various circles ranging from children to adults. The rise of the use of traditional medicines in the community, is not in line with available data on who is the highest consumer and how it seems to their health. Aims: Explore public perceptions related to traditional medicine based on sex differences. Method: The method used in this study is an explanatory associative. The research subjects were the people of Purwakarta Regency, West Java Province, which amounted to 137 people. Sampling is done using the conditional sampling method. Research instruments change observation sheets. Results: The results showed that of the 137 respondents had the knowledge and the interests of traditional medicine (enough: 58.3%), believing traditional medicine had the potential to be developed as a health effort (strong: 61.5%), believing in health treatment efforts can heal (Enough: 52.6%), believe that traditional medical practice facilities have not been standardized (enough: 54.3%). Conclusion: The group of women's respondents compared to men's groups has a lower perception of the potential development of traditional medicine, having a lower level of trust in the healing ability of traditional medicine, has a higher level of trust that traditional treatment has not been standardized, but relatively has the same perception Knowledge and Interest for traditional medicine.